Aplicación de una estrategia didáctica “Fomentando la lectura” para mejorar los niveles de comprensión lectora en los estudiantes de 3° grado - Chois Velasquez, Karol Jacquelin (2022)
The professional sufficiency study, called Application of a didactic strategy "Promoting reading" to improve reading comprehension levels in 3rd grade students, aims to promote the reading habit whose benefits will be to improve their vocabulary, paraphrasing, argumentation and inferring content from the text. It is based on the theories of Montessori, Vygotsky and Isabel Solé, which supports the connection of the known subject with the learning process. In relation to the application of a strategy, the comprehension levels reached the proposed goals, executing learning sessions for a bimonthly period. At the end of the pedagogical task, it is evident that the students of the third grade of primary education improved the levels of reading comprehension significantly, obtaining extraordinary achievements at the literal level , because it allowed to retrieve the information cited in the text ; at the inferential level, it referred to the analytical understanding of the text; At the criterial level, it established the comprehension of the text by issuing a value judgment regarding the topic.